THE INFLUENCE OF FINGER PAINTING GAME TO INCREASE WRITING LETTER ABILITY FOR MODERATE RETARDATION LEARNER - Emilia Martadini; Saichudin Saichudin (Department of Special Education, 2016)
The research’s purpose was to analyze the effect of game finger painting toward writing letter ability of moderate retardation learner in SDLB/C. Data which collected was analyzed by using experiment technique with Single Subject Research A-B-A design. Research result showed that after being analyzed among condition, overlap percentage was 0%. Thus, it could be concluded that there was a effect of game finger painting toward writing letter ability of moderate retardation learner.